Synthesis of pyrazine derivative-substituted phthalocyanines: evaluation of their Sono/photochemical and antimicrobial properties supported by DFT studies - Canibek, Umut Burak; Gunsel, Armagan; Gokcil, Gokce; Atmaca, Goknur Yasa; Tuzun, Burak; Aydemir, Ozlem; Gunsel, Hilal; Bilgicli, Ahmet T.; Erdogmus, Ali; Yarasir, M. Nilufer (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2026)
In this study, the novel 3-(2-(pyrazin-2-yl) ethylthio) phthalonitrile (1) as starting material was synthesized and its non-peripherally tetra- pyrazine derivative -substituted phthalocynine compound (2) was synthesized for the first time. Then, its water soluble-quaternized phthalocyanine compound (2a) was prepared. All compounds used were characterized with various spectroscopic methods such as UV-Vis, FT-IR, 1H NMR, 13C NMR, SEM and MALDI-TOF MS. The potential of photochemical and sono-photochemical techniques to enhance singlet oxygen production-an essential component in photodynamic therapy-was evaluated. The newly synthesized phthalocynines displayed significant singlet oxygen quantum efficiencies. Among them, the phthalocynine (2) and (2a) yielded Phi Delta values of 0.53 and 0.14 for the photochemical method, while the corresponding values under sono-photochemical conditions were 0.67 and 0.26. Additionally, the antimicrobial efficacy of the newly synthesized phthalocyanine (Pc) derivatives (2) and (2a) was evaluated using the broth microdilution method against a broader panel of Gram-positive and Gram-negative bacterial strains, including Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Both compounds exhibited measurable antibacterial activity, with minimum inhibitory concentrations (MICs) ranging from 4 to 32 & micro;g/mL. Notably, compound (2a) demonstrated the strongest effect against E. faecalis (MIC = 4 & micro;g/mL) and S. aureus (MIC = 8 & micro;g/mL), while also showing enhanced inhibition of K. pneumoniae (MIC = 8 & micro;g/mL) compared to compound (2) (MIC = 32 & micro;g/mL). For E. coli and P. aeruginosa, both derivatives displayed similar MIC values of 16 & micro;g/mL. These results indicate that quaternization significantly improves the antibacterial potency of the phthalocyanine derivative, particularly against E. faecalis and K. pneumoniae. Calculations of the ligand (1) and its phthalocyanine (Pc) derivatives (2) and (2a) were carried out with Gaussian software program at B3LYP, HF, and M062X level in 6-31 g, 6-31++g, and 6-31++g(d,p) basis sets. Afterwards, the activities of the molecules against various proteins were compared and their interactions were investigated.
Keywords: Phthalocyanine; Synthesis; Sono/photochemical; Antimicrobial; DFT; ESCHERICHIA-COLI; ANTIOXIDANT; METALLOPHTHALOCYANINES; AGGREGATION; BEHAVIOR; Biochemistry & Molecular Biology; Chemistry